Analysis of External Factors Based on Porter's Five Forces Method at PT Gipan Metal Teknik Indonesia - Pranoto, Ari; Indradewa, Rhian (Sahabat Publikasi, 2024)
The industrial company providing and fabricating abrasion-resistant steel PT Gipan Metal Teknik Indonesia (PT GMTI) will face competition in the business, so the company must increase efficiency and optimize its potential. This study aims to determine the competitive advantage strategy of PT GMTI based on Porter's Five Forces method. Analysis of external factors as a planning strategy to find out opportunities and threats in running business processes so that they can affect the sustainability of the company. Michael A. Porter describes the five forces module as an analytical tool in industrial competition. The results of this analysis are in the form of external factors of the company in facing the Competitive Force used by the company in facing business competition. External factors faced by PT GMTI in running its business based on Porter's Five Forces method are a) Threat of New Entrans namely the need for company capital and government regulations, b) Rivalry Among Existing Competitors namely the quality of products offered and marketed, c) Bargaining Power of Buyers namely the number of similar competitors, d) Bargaining Power of Suppliers namely the price of raw materials from suppliers, e) Threat of Subtitute Products, namely the quality of substitute products. The results of this study show that the strategy that can be developed by PT GMTI is to increase business capital and training employees so that the company can develop and maintain the quality of services and products for business continuity. The determination of variables used in Porter's Five Forces analysis is based on the experience of one of our members who works as a supplier of abrasion-resistant materials and also works in one of the heavy equipment companies in Indonesia.